(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper discussed the role of the library in education by establishing a relationship between ‘Library’ and ‘Education’. ‘Education’ and ‘Library’ are two inseparable and one cannot exist alone in the absence of the other. In other words, one survives as long as the other exists. This relationship and dependence on each other came from the birth of human civilization into economic success through an evolutionary process in accord with various needs, changes and circumstances of various stages of human life.